Relationship between horizontal collectivism and social network influence among college students: mediating effect of self-monitoring and moderating effect of self-efficacy - Yuan, Ye; Du, Jinchen; Yang, Ke; Ge, Yifan; Ma, Yixuan; Mao, Huapei; Xiang, Min; Wu, Daili (Frontiers in Psychology, 2024)
Background The aim of the present study was to investigate the intrinsic relationship between cultural values and social network index among college students. In addition, the present study explored the mediating role of self-monitoring in the relationship between horizontal collectivism cultural values and social network index, as well as the moderating role of self-efficacy, to provide a theoretical approach based on the intrinsic mechanism for college students to establish a good social network. Methods A simple random cluster sampling method was used to investigate 376 college students with cultural values scale, self-monitoring scale, self-efficacy scale, and social network index scale, structural equation model was constructed using M-plus and SPSS. Results The result indicated that individual horizontal collectivist cultural values positively predict social network index (β = 0.477). Self-monitoring plays an intermediary role between cultural values and social network index, and self-efficacy plays a moderating role between self-monitoring and social network index. Conclusion The level of an individual’s social network activity is affected by the cultural values of horizontal collectivism and self-monitoring. Improving individual self-monitoring ability and self-efficacy can effectively improve the interpersonal relationships of college students.